Olam International Ltd : building an Asian multinational - Williamson, Peter J., (SAGE knowledge. Cases., 2016)
This case traces the rise of Olam International from humble beginnings in Africa to become a global player, headquartered in Singapore. It examines the processes of growth, internationalisation and diversification into 'adjacent' businesses as the company built a multinational company from Asia through 'greenfield' expansion, alliances and acquisitions.